Changes in Weed Communities of Spring Wheat Crops of Buenos Aires Province of Argentina - Scursoni, Julio Alejandro (2014)
During 2004 to 2008, weed surveys were conducted in 373 wheat fields of two different cropped areas (southwest [SW] and southeast [SE]) of the southern region of Buenos Aires Province of Argentina where different weed communities were expected because of changes in cropping practices over time, including tillage, crop sequence, fertilizers, and herbicides applied. Weed communities differed between regions, with greater numbers of native species for the SW. Weed community diversity was also greater for the SW region, probably due to the more diverse land use that resulted in greater landscape heterogeneity. Rush skeletonweed, sand rocket, yellow starthistle and turnipseed occurred at higher constancy (proportion of fields in which a given species is present) in the SW region, whereas common chickweed, false bishop's weed, corn speedwell, and common lambsquarters were present more frequently in the SE region. Compared with the 1982 survey, constancy of weeds increased, but those species with high constancy in 1982 were also with high constancy in the recent surveys. Diversity (species richness) was greater in conventional than in a no-tillage system. The constancy of Italian ryegrass, sand rocket, and yellow starthistle was lower under no-till than conventional tillage. Surveys allow identification of changes in weed community related to different agricultural systems. Rotation of crops and livestock avoid the homogenization of the environment at the landscape level. Management strategies will be necessary to prevent the increase of weeds populations' size, preserving plant diversity and the properties of the agroecosystem.